رند ؔ لکھنویؔ : ایک منفرد کلاسیکی غزل گو: Rind Lakhnavī: A Different Classical Ghazal Poet (Al-Qamar, 2021)
Rind was a famous disciple of Aātish- His poetry depicts lakhnawī classical thoughts.  His Diwān consisted different styles of poetry like Ghazal, Masnavī, Rubaī, Qaṭ’āt and wasokht etc. But his main field of poetry is Ghazl. His Ghazal has two different shades of lakhnawī culture, first which was the general trend of the society and second is his own variation which he adapts side by side the general trend- These typical variations like simplicity short rhythm clearly seen in Meer,s  poetry- In that’s way he proved himself a versatile poet which amused his readers and remind them the typical style of Meer. We simply tell him the true follower of Meer. In this article various aspects of his poetry (both style and subject) will be highlighted.
Keywords: Imām Mūsa Kāzim; Muhammad Yousuf blind; Faiz Aābad; Bahū Begum; Nawwāb; Shuja-ud- Dola